Accounting restatements and external financing choices - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2012)
There is little research on how accounting information quality affects firms’ external financing choices. In this paper, we use accounting restatement as a proxy for the reduced credibility of accounting information and investigate how restatement affects a firm’s external financing choices. We find that for restatement firms that obtain external financing after restatements, they rely more on debt financing, especially private debt financing, and less on equity financing. The increase in debt financing is more pronounced for firms with more severe restatements. Our evidence indicates that accounting quality affects capital providers’ resource allocations and that debt holders help alleviate information problems after accounting restatements.